(untitled) (Nexo Revista Científica, 2020)
Apical buds obtained from Asparagus plant vitro culture and somatic embryos obtained from stem cultivation, explants in MS medium supplemented with mg¹ᶫ 1, 2, 4-D and mg¹ᶫ 1 and Kinetin have been used in this research to produce artificial seeds. We encapsulated apical buds and somatic embryo using 2% sodium alginate and calcium chloride to prepare the artificial seeds. We placed artificial seeds at room temperature (about 25 ° C), in the cold, the temperature of 4 ° C and -18 ° C for different times (15,30,60,90 days) and evaluated the growing power of these seeds in MS and ½MS mediums for further investigations about the viability of seeds. The highest conversion percentage of seedlings in encapsulated embryos (70.01) was related to seed harvested from embryos treated with BA and the highest conversion percentage of seedlings in apical buds (96.54) was obtained from cultivated untreated seeds in MS medium. Encapsulated arteries and buds maintained germination energy and viability with increasing storage time after 90 days of storage at 4 and 25 ° C despite viability reduction while un-capsulated embryos and buds completely lost viability after 60 days of storage at 4 and 25 ° C and seeds stored at -18 ° C completely lost viability after 15 days of storage. In general, the percentage of seed germination and conversion to seedling is higher in seeds cultivated in MS medium compared to seeds cultivated in ½MS medium.